PENGARUH PROMOSI ONLINE, PERSEPSI HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DI MASA PANDEMI COVID 19 - Tirtana, Diovany; Turmudhi, Anis (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2021)
This study explores the perception of online promotion, price and product quality on purchasing decisions during the Covid 19 Pandemic. The sample in this study is the community in the city of Semarang. Explanatory research using a quantitative approach. Primary data were collected through questionnaires and analyzed using multiple linear with Likert Scale. These results indicate that during the pandemic, product quality has a very strong influence on purchasing decisions. Furthermore, the buyer's decision becomes better for consumers who are able to recognize products from online promotions. In addition, online promotions that present prices provide an opportunity for consumers to make price comparisons. So this research is able to prove that online promotion, price perception and product quality are important considerations for consumers to make online purchases during the current Pandemic.